A Theoretical Framework for Reinforcing Religious Moderation through Christian Religious Education among Digital Natives in the Era of Digital Extremism - Laoli, Opriyaman; Lawolo, Nirta (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
This research aims to develop a conceptual framework to strengthen religious moderation through Christian Religious Education, specifically addressing the digital native generation and the challenges of digital extremism. Motivated by Generation Z's tendency to seek religious information through digital media-which increases their vulnerability to extremism and this study employs a descriptive qualitative method with a literature review approach. Data were collected from various relevant sources, analyzed through thematic categorization and descriptive interpretation, and validated using source triangulation to ensure reliability. The results identified four theoretical strategies: Digital Counter-Narrative Workshop, Interfaith Digital Dialogue, Digital Storytelling, and Faith-Based Digital Citizenship Certification. The novelty of this study lies in integrating the principles of religious moderation-rooted in Christian values such as love and Imago Dei-into a digital learning framework adapted to the characteristics of the digital native generation, thereby addressing gaps in previous research lacking a comprehensive approach. This research provides implications for the development of religious education concepts relevant to the digital age, reinforcing the role of PAK in shaping a solid and harmonious faith identity amid diversity, and preventing exposure to extremist content that could distort the religious understanding of young Christians